Daily scriptures : 365 readings in Hebrew, Greek, and Latin - Cerone, Jacob N. (Jacob Nathaniel), 1985-; Fisher, Matthew C., 1966- (Grand Rapids, Michigan : William B. Eerdmans Publishing Company, 2021)
"A collection of daily Bible readings in Hebrew, Greek, and Latin with lexical aids, intended for use both as a devotional and as a way of maintaining knowledge of biblical languages"--
Includes bibliographical references (pages 369-370) and index.